2010
DOI: 10.1007/s00264-009-0932-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an intramedullary implant with a static magnetic field on the healing of the osteotomised rabbit femur

Abstract: Static magnetic fields are a type of electromagnetic fields used in clinical practice. To ascertain what effect a static magnetic intramedullary device implanted in the rabbit femur had on fracture healing, 20 male New Zealand white rabbits with magnetic/nonmagnetic intramedullary implants were examined histologically, radiologically and for bone mineral density. Three groups were constituted according to the poles of the magnets. During surgery the intramedullary device was driven into the medulla. A femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
1
35
0
2
Order By: Relevance
“…Finally, because SMF is a single physical factor, it can result less side effects comparing with varieties of physical factors such as PEMF. Since SMF has been shown to be effective in facilitating ununited fracture repair 16) and preventing bone loss 17) , it has received considerable attention about the biological effect of SMF on bone cells. A certain intensity SMF has been reported that it can significantly enhance osteoblast differentiation in vitro [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because SMF is a single physical factor, it can result less side effects comparing with varieties of physical factors such as PEMF. Since SMF has been shown to be effective in facilitating ununited fracture repair 16) and preventing bone loss 17) , it has received considerable attention about the biological effect of SMF on bone cells. A certain intensity SMF has been reported that it can significantly enhance osteoblast differentiation in vitro [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmaya göre, SMA overektomize sıçanların osteoporotik omurgalarının KMY değerlerini artırmıştır. Aydın ve Bezer [13] SMA içeren intramedüller çivi-nin osteotomize sıçan femurunun iyileşmesi üzerine etkilerini araştırmışlardır. Bu araştırma sonucunda, SMA'nın erken kırık iyileşmesinde osteogenezisi baş-lattığı sonucuna varmışlardır.…”
unclassified
“…It has been shown that SMF affects osteoblastic maturation and differentiation by upregulating local factors and inducing membrane reorientation and distortion. 20 In addition, there is evidence that SMF caused higher cell attachment and proliferation on the machined titanium surface. 27 Furthermore, effects of electromagnetic fields on cell mitotic activity, 21 changes in cell signaling pathways, 27 upregulating synthesis of transforming growth factor-b1, and increase in extracellular matrix proteins could be considered as other factors underlying the action mechanism of SMF on bone healing.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported that magnetic fields could enhance bone formation. 20,24,28,29 Shigino et al 24 showed that electromagnetic fields stimulate bone healing around endosseous implants in the dog mandible. Matsumoto et al 29 reported an enhanced bone formation around dental implants using PEMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation